Review of magnetostrictive vibration energy harvesters - Deng, Zhangxian; Dapino, Marcelo J (Smart materials and structures, 2017)
The field of energy harvesting has grown concurrently with the rapid development of portable and wireless electronics in which reliable and long-lasting power sources are required. Electrochemical batteries have a limited lifespan and require periodic recharging. In contrast, vibration energy harvesters can supply uninterrupted power by scavenging useful electrical energy from ambient structural vibrations. This article reviews the current state of vibration energy harvesters based on magnetostrictive materials, especially Terfenol-D and Galfenol. Existing magnetostrictive harvester designs are compared in terms of various performance metrics. Advanced techniques that can reduce device size and improve performance are presented. Models for magnetostrictive devices are summarized to guide future harvester designs.